2021
DOI: 10.3390/jcm10071367
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint Inhibitors as High-Grade Gliomas Treatment: State of the Art and Future Perspectives

Abstract: Glioblastoma (GBM) is the most common and aggressive malignant brain tumor in adults. Despite significant efforts, no therapies have demonstrated valuable survival benefit beyond the current standard of care. Immune checkpoint inhibitors (ICI) have revolutionized the treatment landscape and improved patient survival in many advanced malignancies. Unfortunately, these clinical successes have not been replicated in the neuro-oncology field so far. This review summarizes the status of ICI investigation in high-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…One potential explanation for this finding is that the decline in lymphocytes after cytotoxic antineoplastic therapy may enhance the ability of surviving tumors to evade the immune system. Lymphocytes are considered essential for the suppression of tumor development within the immune microenvironment and as regulators of the immune surveillance process, thereby leading to poor prognosis in high-grade gliomas ( 2 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential explanation for this finding is that the decline in lymphocytes after cytotoxic antineoplastic therapy may enhance the ability of surviving tumors to evade the immune system. Lymphocytes are considered essential for the suppression of tumor development within the immune microenvironment and as regulators of the immune surveillance process, thereby leading to poor prognosis in high-grade gliomas ( 2 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing clinical trials are aiming to add nivolumab, an immune checkpoint inhibitor against programmed cell death 1 (PD-1), a pathway that downregulates the immune system, to RT [Checkmate 498, (NCT02617589)] or RT/TMZ [Checkmate 548 (NCT02667587)]. However, the latest results have suggested that nivolumab + RT or nivolumab + RT + TMZ did not show better efficacy than standard treatment, possibly due to lymphopenia ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical responses are extremely variable from one cancer to another, and the durability of the response is also very variable from one patient to another. Spectacular responses have been observed in NSCLC and melanoma, whereas the response rate is much more limited in neuro-oncology, for example [ 3 ]. Similarly, PD-1/PD-L1 checkpoint inhibitors are not very effective in treating acute myeloid leukemia [ 4 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
“…However, immunogenic effects of RT may be counterbalanced by evasive mechanisms in the TME, including induction of angiogenic and fibrogenic growth factors such as TGF-b, accompanied by activation of cancer-associated fibroblasts (CAFs) and enhanced tissue remodeling, recruitment of immunosuppressive cells, induction of immune checkpoints (e.g., PD-L1), and, consequently, T cell exhaustion and tumor immune tolerance (Abdollahi and Folkman, 2010;Barker et al, 2015;Twyman-Saint Victor et al, 2015;Vanpouille-Box et al, 2015). These factors may account for the lack of clinical activity and abscopal effects seen in immune-cold or immune-excluded tumors after dual combination of RT and anti-TGF-b or ICIs, respectively (Wick et al, 2020;Formenti et al, 2018;Persico et al, 2021).…”
Section: Introductionmentioning
confidence: 99%